Local wisdom for mitigating HIV stigma and discrimination in Palopo, Indonesia: A qualitative study - Adam, Arlin; Zainuddin, Zainuddin; Ibrahim, Irviani Anwar (Sociality: Journal of Public Health Service, 2025)
HIV-related stigma and discrimination remain persistent barriers to HIV prevention and treatment, and prior studies show that biomedical services alone are often insufficient when stigma disrupts testing, disclosure, and retention in care, highlighting the novelty of culturally grounded stigma-mitigation strategies. This study examined the role of Bugis–Luwu local wisdom as a health intervention resource to reduce stigma and discrimination toward people living with HIV (PLHIV) in Palopo, Indonesia, and identified cultural mechanisms that can be integrated into HIV service programs. A phenomenological qualitative design was applied with in-depth interviews, participatory observation, and cultural document review involving PLHIV, customary leaders, religious leaders, health workers, community cadres, and HIV program managers. Data were analyzed using Braun and Clarke’s thematic analysis, supported by triangulation and member checking. Findings indicate three interlinked cultural mechanisms with intervention relevance: (1) social-ethical values (sipakatau, sipakalebbi, and sipakainge) that reinforce dignity, respect, and non-judgmental guidance; (2) musyawarah adat as a restorative forum to resolve conflict and reintegrate PLHIV; and (3) the moral authority of customary and religious leaders as trusted messengers capable of reframing HIV away from moral blame and toward public health support. Key challenges include misconceptions about HIV transmission, limited cultural integration in formal health programs, and social change weakening customary practices. Integrating local wisdom into health communication, community mobilization, and culturally safe service delivery may strengthen acceptability, sustainability, and equity of HIV interventions in Palopo.